(3GdfGaY jhe GdMTQs - (3GdSjhQj, GdMdj, GdCSOj, CHh YHO Gddg, TQa GdOjf, ebOGO Hf YHO Gddg Hf eMeO Hf GdMSjf, J (B826s
(3ChdgG (B:s
(3ChdgG(B: (3GdbSe GdChd adPdc bGd jLH Ydi YGeI Gdecdajf (B... (3ef ef GdCMdGa hhbY GdNha hGLH dCfg des
(3BNQgG (B:s
(3BNQgG(B: (3GdQGHY ef GdBeQ hGdfGgj ef GdVQO GdMGUd HSHH GdCeQ hGdfgj eG (B... (3Ch Edi CMO ef GdeSdejf aEf ZdH YfOgeG MUhd Pdc GQJaY GdhLhH CjkVG hjLHGf HGdbdH hGddSGf hGdHOQ dG jfJbd Edi GdCUYH eY GfLGY GdCSgds
(3jdjgG COYjI hMOjK bOSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 282s
(3GdPQjYI, L (B24: 13s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJhMjO hGdedd hGdfMds